Solve for x
x=16
Graph
Share
Copied to clipboard
-\sqrt{x}=-\left(x-12\right)
Subtract x-12 from both sides of the equation.
\sqrt{x}=x-12
Cancel out -1 on both sides.
\left(\sqrt{x}\right)^{2}=\left(x-12\right)^{2}
Square both sides of the equation.
x=\left(x-12\right)^{2}
Calculate \sqrt{x} to the power of 2 and get x.
x=x^{2}-24x+144
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(x-12\right)^{2}.
x-x^{2}=-24x+144
Subtract x^{2} from both sides.
x-x^{2}+24x=144
Add 24x to both sides.
25x-x^{2}=144
Combine x and 24x to get 25x.
25x-x^{2}-144=0
Subtract 144 from both sides.
-x^{2}+25x-144=0
Rearrange the polynomial to put it in standard form. Place the terms in order from highest to lowest power.
a+b=25 ab=-\left(-144\right)=144
To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as -x^{2}+ax+bx-144. To find a and b, set up a system to be solved.
1,144 2,72 3,48 4,36 6,24 8,18 9,16 12,12
Since ab is positive, a and b have the same sign. Since a+b is positive, a and b are both positive. List all such integer pairs that give product 144.
1+144=145 2+72=74 3+48=51 4+36=40 6+24=30 8+18=26 9+16=25 12+12=24
Calculate the sum for each pair.
a=16 b=9
The solution is the pair that gives sum 25.
\left(-x^{2}+16x\right)+\left(9x-144\right)
Rewrite -x^{2}+25x-144 as \left(-x^{2}+16x\right)+\left(9x-144\right).
-x\left(x-16\right)+9\left(x-16\right)
Factor out -x in the first and 9 in the second group.
\left(x-16\right)\left(-x+9\right)
Factor out common term x-16 by using distributive property.
x=16 x=9
To find equation solutions, solve x-16=0 and -x+9=0.
16-\sqrt{16}-12=0
Substitute 16 for x in the equation x-\sqrt{x}-12=0.
0=0
Simplify. The value x=16 satisfies the equation.
9-\sqrt{9}-12=0
Substitute 9 for x in the equation x-\sqrt{x}-12=0.
-6=0
Simplify. The value x=9 does not satisfy the equation.
x=16
Equation \sqrt{x}=x-12 has a unique solution.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}